THE UTILIZATION OF BAMBOO AS A REPLACEMENT OF STEEL FOR BUILDING STRUCTURES - Hartati Kapita; Fitro Darwis (International Journal of Education, Information Technology, and Others, 2018)
Bamboo can be aligned with steel due to it has a power of pull and strength so that it can bear a flexible moment and has resistance toward the wind and earthquakes. The use of bamboo can be utilized as an alternative material for the substitutes of steel for the construction of multi-storey building structures because it has the same properties. In this study it is still limited to beam and column modeling for building structures by testing flexural strength and bamboo press. This study is laboratory experiments. The types of bamboo used in this study are petung bamboo, wulung bamboo, gombong bamboo and ori bamboo. Based on the results the ori bamboo has a fairly good flexural strength when used as reinforcement as it has a fairly good level of flexibility when given a load. While for petung bamboo and wulung bamboo, the strength of flexural produced is not too good when given the burden. The four types of bamboo, namely petung bamboo, ori bamboo, wulung bamboo and gombong bamboo can be utilized as reinforcement for the structures of simple building.